FMTVDM-Breast Cancers Diagnostic Doorway from Qualitative to Quantitative Measurement, Care and Treatment - Richard M Fleming; Matthew R Fleming; William C Dooley (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
Clinical efforts to diagnostically evaluate women-and men-with breast cancer have resulted in various degrees of success. The use of external radiographic sources to look for tissue abnormalities-mammography - has according to the Cochrane Collaboration not been able to demonstrate a reduction in mortality [1]; a position also held by the National Cancer Institute and The Canadian Trial [2].